A Case-Control Study of the Role of Cold Symptoms and other Historical Triggering Factors in Asthma Exacerbations - Susan M Tarlo; Irvin Broder; Paul Corey; Moira Chan-Yeung; Alexander Ferguson; Allan Becker; Peter Warren; F Estelle R Simons; Christopher Sherlock; Marilyn Okada; Jure Manfreda (Canadian Respiratory Journal)
BACKGROUND: Asthma exacerbations can be provoked by many triggers such as allergens, respiratory irritants and viral infections. The relative importance of these has not been prospectively documented in a case-control study.